Increased Risk of Vitamin D Deficiency Among HIV-Infected Individuals: A Systematic Review and Meta-Analysis - Wang, Yingying; Huang, Xiaojie; Wu, Yaxin; Li, Aixin; Tian, Yakun; Ren, Meixin; Li, Zhen; Zhang, Tong; Wu, Hao; Wang, Wen (Frontiers in Nutrition, 2021)
Background: Human immunodeficiency virus (HIV) infection is a heavy burden worldwide. Observational studies have reported a high prevalence of vitamin D deficiency (VDD) among people living with HIV (PLWH). However, its deficiency is also a global health problem. Therefore, we conducted a meta-analysis and systemic review to compare differences between HIV-infected subjects and non-HIV-infected subjects. Methods: We searched PubMed, Web of Science, Embase, and Cochrane library. We extracted data, including demographic information, study type, vitamin D-related values, and HIV-related values, ultimately including 15 studies after removing duplicates and screening titles, abstracts, and full texts and finally performing a meta-analysis in terms of vitamin D level and vitamin D deficiency prevalence. Results: Regarding VDD prevalence, the HIV versus the non-HIV group had an odds ratio of 1.502 (95% CI, 1.023 to 2.205; P=0.038). In the subgroup analysis, the odds ratios were 1.647 (95% CI, 1.020 to 2.659; P=0.041; I2=94.568) from 7 studies (age over 40), 2.120 (95% CI, 1.122 to 4.008; P=0.021; I2=0.000) from 2 studies (BMI less than or equal to 25), 1.805 (95% CI, 1.373 to 2.372; P=0.042; I2=74.576) from 7 studies (latitude less than 40),2.120 (95% CI,1.122 to 4.088; P=0.021; I2=0.000) from 2 studies (only included male participants) , and 2.296 (95% CI,1.287 to 4.097; P=0.005; I2=19.927) from 3 studies (only included ART-experienced participants). Thirteen studies were deemed to have moderate quality, while two had high quality. Conclusions: ART, older age, lower BMI, lower latitude and male sex may present risk factors for VDD in PLWH.